2010
DOI: 10.1007/s11046-009-9267-8
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostoma tsotsi sp. nov., A Wound-infesting Fungus of Hardwood Trees in Africa

Abstract: Polymorphic sequence-characterised marker assays from a recent diversity study on the Ascomycete fungus Ophiostoma quercus reported that some isolates from Africa were genetically distinct from O. quercus. In the present study, these African isolates were compared with authentic O. quercus isolates by evaluating morphological characters, growth in culture, mating compatibility and DNA sequence data. The isolates from Africa were morphologically similar to O. quercus, presenting Pesotum and Sporothrix synanamor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 34 publications
(35 reference statements)
3
34
0
Order By: Relevance
“…Similarly, Yin et al (2016) distinguished between the O. ulmi complex and a newly defined O. piceae complex that includes only conifer-associated fungi. Grobbelaar et al (2010) showed that BT and EF sequences are needed in addition to ITS to resolve species level questions in the O. ulmi complex. Our analyses of these three gene regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Yin et al (2016) distinguished between the O. ulmi complex and a newly defined O. piceae complex that includes only conifer-associated fungi. Grobbelaar et al (2010) showed that BT and EF sequences are needed in addition to ITS to resolve species level questions in the O. ulmi complex. Our analyses of these three gene regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the O. ulmi complex includes Ophiostoma ulmi and O. novo-ulmi, the causal agents of the Dutch elm disease (Brasier 1991), most species in the complex, including O. tsotsi, are known as non-pathogenic sapstain fungi on hardwood trees De Beer et al 2003;Grobbelaar et al 2010). Inoculation studies with O. tsotsi on young…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to obtain sexual structures for morphological descriptions of species revealed by the phylogenetic analyses, crosses between different isolates of the same species were made in all possible combinations on Petri dishes to which autoclaved host tree twigs had been added (Grobbelaar et al (2010). To serve as controls, isolates were inoculated individually on Petri dishes.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Isolates of opposite mating type of the same species were paired with each other in all possible combinations. These pairings were done on water agar with sterilized pieces of pine wood using the technique described by Grobbelaar et al (2010), and incubated for 3-4 months at 25°C. Interspecific crosses were also performed using isolates of four morphologically indistinguishable species (L. bhutanense, L. sinoprocerum, L. gracile and L. latens).…”
Section: Morphology Growth and Mating Studiesmentioning
confidence: 99%